Coral Health and Disease in the Spermonde Archipelago and Wakatobi, Sulawesi - Muller, Erinn M; Raymundo, Laurie J; Willis, Bette L; Hapkayla, Jessica; Yusuf, Syafyudin; Wilson, Joanne R; Harvell, Drew C (Journal of Indonesian Coral Reefs, 2012)
Preliminary surveys for coral disease were conducted in October 2011 as part of the first Indonesian coral health workshop in Barranglompo Island, part of the Spermonde Islands, South Sulawesi, Indonesia. Previous coral disease surveys conducted in Wakatobi National Park (WNP), South-East Sulawesi in 2005 and 2007, and qualitative surveys in April 2011, are included here to provide an overview of what is known about coral disease in Sulawesi and to compare results with reports from other regions of the world. On all reefs surveyed in these two locations, levels of coral disease were relatively low compared with global averages from other locations. In preliminary surveys of Spermonde reefs, the most significant syndrome detected was white syndromes, which affected 13 different coral genera. The most significant syndromes detected in WNP were white syndromes, black band disease, and a yellow tissue discoloration syndrome that was similar macroscopically to Caribbean yellow band disease. Although overall coral disease prevalence was low in Barranglompo and WNP, there is the potential for greater impacts of coral disease as anthropogenic influences increase and the oceans continue to warm. This study provides preliminary baseline data on the impact of coral disease within the reefs of Sulawesi, Indonesia, the center of coral reef biodiversity.